Biotechnological production of crocetin and crocins using a carotenoid cleavage dioxygenase (CCD4) from Nyctanthes arbor-tristis - Morote, Lucía; Moreno Giménez, Elena; López Jiménez, Alberto José; Rubio-Moraga, Ángela; Aragonés, Verónica; Ahrazem, Oussama; Daròs, José-Antonio; Gómez-Gómez, Lourdes (Frontiers in Plant Science, 2025)
Crocins are hydrophilic crocetin esters composed of a linear chain with glucose molecules added at the end. Crocins and crocetin are used as cosmetic agents and effective pharmaceuticals for the treatment of several diseases. Crocetin dialdehyde, an immediate precursor of crocetin, is derived by C7-C8(C7'-C8′) cleavage of carotenoids, which is synthesized in a few plant species including Crocus sativus or Nyctanthes arbor-tristis. We investigated the genome of N. arbor-tristis to identify the enzyme responsible for the biosynthesis of crocetin dialdehyde in this plant and showed that an enzyme from the CCD4 subfamily catalyzed the cleavage of zeaxanthin to produce this apocarotenoid. This enzyme, NatCCD4.1, was further used for the microbial production of crocetin dialdehyde in a two-phase culture system resulting in a titer of 109.2 ± 3.23 mg/L, which is the highest crocetin dialdehyde yield reported in bacteria so far, higher than that obtained when using the enzyme from C. sativus, CsCCD2. In addition, a viral vector derived from tobacco etch virus was used to express NatCCD4.1 in Nicotiana benthamiana plants, triggering a crocin accumulation of 2.32 ± 0.69 mg/g dry weight, with 96.61% reduction in zeaxanthin levels, together with a decrease in chlorophylls resulting in a bright yellow pigmentation of infected leaves. Our results offer new insights into the biosynthesis of crocins in crocin-producing species. Additionally, NatCCD4.1 proves to be an excellent tool for metabolic engineering, enhancing crocetin and crocin production in various heterologous systems.